From Within and Without: Gender, agency and sustainable management of non-timber forest products in two Indian States - Jalonen, Riina; Ferraz Ziegert, Rafaella; Lamers, Hugo A.H.; Hegde, Narasimha (Springer, 2023)
Non-timber forest products (NTFP) from trees are often collected using unsustainable practices, which contributes to the species’ decline and affects the livelihoods and wellbeing of the most forest-dependent groups, such as women, ethnic minorities and the landless. Here we assess opportunities to improve the sustainability of NTFP collection practices across two landscapes in India, using an agency perspective where male and female NTFP collectors themselves identified and evaluated practices and potential interventions for species of their choice. We developed a framework for identifying community-based solutions for NTFP management and carried out participatory exercises in gender-segregated groups in ten rural communities across two states. Unsustainable collection practices such as cutting branches to collect fruits were somewhat more common among women than men, and more common in the more degraded landscape with weaker forest management institutions. Participants described ecological and economic impacts of collection practices in detail, including impacts on future yields, regeneration and product prices. Proposed solutions to improve NTFP management in the less degraded landscape were focused on incentivising sustainable use and working through village institutions, external actors, or both in collaboration. In the more degraded landscape, participants emphasised sanctions and did not frequently propose the existing village institutions to take action. Women proposed collaboration with external actors less often than men. The results indicate that agency perspectives are useful in stimulating discussion about locally relevant NTFP management options, but that social and gender norms and poor relationships with forestry authorities constrain the agency of vulnerable groups in identifying opportunities for change.